Latino Alzheimer's Caregiving: Neither a Burden nor a "Carga" - Lyda Arevalo-flechas (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Caregivers provide care for relatives with Alzheimer’s disease at an emotional and physical cost to themselves. Language and cultural factors influence how caregivers are impacted by their role, yet the role that culture and language play on a person’s perception of caregiving has not been adequately explored. Not having a Spanish equivalent for the expression “caregiver burden.” raises concern when this concept is translated to the wordcargaand used to describe Latino caregiving.Aim:To describe the perceptions of the caregiving experience of bilingual Latino/Hispanic family caregivers of relatives living with Alzheimer’s disease, and explore the language used in their narratives.Method:Data collection and analyses followed a modified Spradley ethnographic methodology. Semi-structured interviews were conducted, and prolonged participant observation and artifacts provided rich data.Results:All caregivers described their experience as difficult, but not as a burden or carga. Caregiving was described as an honorable opportunity to accomplish two culturally prescribed goals: caregiver satisfaction, and caregiver duty fulfillment. Three overarching themes were elucidated: caregiving has consequences, caregiving fulfills a duty, and caregiving is satisfying. The main consequences were: caregiving is physically challenging, caregiving is emotionally draining, and caregiving is financially detrimental. Caregiving fulfills a duty had two main components: Caregiving is my duty, and caregiving is learned. Caregiving is satisfying had three components: Caregiving is my opportunity to give back, knowing that I am doing my best, and a sacrifice.Conclusion:Data support the formulation of a conceptual orientation of the Latino caregiving experience.